2021
DOI: 10.18632/aging.202853
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of genomic and immunological profiles in Chinese and Western hepatocellular carcinoma populations

Abstract: In this study, we explored the genomic and immune cell infiltration profiles among four distinct Hepatocellular carcinoma (HCC) types. This study included 100 patients (all tumors and adjacent liver tissues received WES sequencing) with HCC from the West China Hospital (WCH) and patients were divided into WCH-HBV-HCC group and WCH-NonHBV-HCC group. Additionally, this study included 106 HBV-related HCC (TCGA-HBV-HCC) and 69 alcoholic HCC (TCGA-Alcol-HCC) patients from the TCGA. We analyzed the high-frequency ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Many studies have investigated the relationship between TMB and the modulation of tumoral immunity. A WES analysis of tumoral and peritumoral tissues collected from 100 Chinese HCC patients and 175 HCC patients from the TCGA revealed that HBV-related HCC had a low immune cell infiltration and TP53 mutation, but TMB was not associated with immune infiltration in HBV- and alcoholic-related HCC patients of the TCGA cohort [ 78 ]. At variance, the level of copy number variation seemed to be more predictive of immune infiltration than TMB, even if a great heterogeneity among all the analyzed groups of HCC patients was observed.…”
Section: Tmb and Immune Tmementioning
confidence: 99%
“…Many studies have investigated the relationship between TMB and the modulation of tumoral immunity. A WES analysis of tumoral and peritumoral tissues collected from 100 Chinese HCC patients and 175 HCC patients from the TCGA revealed that HBV-related HCC had a low immune cell infiltration and TP53 mutation, but TMB was not associated with immune infiltration in HBV- and alcoholic-related HCC patients of the TCGA cohort [ 78 ]. At variance, the level of copy number variation seemed to be more predictive of immune infiltration than TMB, even if a great heterogeneity among all the analyzed groups of HCC patients was observed.…”
Section: Tmb and Immune Tmementioning
confidence: 99%
“…The gill mucosa is an important immune barrier, including innate and adaptive immunity [ 46 , 47 ]. Lysozyme is the widely distributed enzyme of the innate immune system that exhibits antibacterial activity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The approval of Lenvatinib in 2018 further solidified the role of kinase inhibitors (KIs) in the first-line treatment of advanced HCC. In a preclinical study, Sorafenib showed better antitumor activity in TP53 wild-type HCC, while Lenvatinib is more sensitive in HCCs with TP53 mutation [65,66]. However, the therapeutic effects of both drugs are far from satisfactory.…”
Section: Sorafenib Lenvatinib Donafenib and Rivoceranibmentioning
confidence: 99%